Translation Analysis In Sentence Patterns Found In The Novel Entitled “The Prince” - I Made juliarta (Denpasar Institute, 2023)
This study aims to: (i) analyze the tree diagram structure of sentence patterns found in the novel entitled “The Prince”, (ii) analyze the types of translation shifts of sentence patterns in the translation process found in the novel entitled “The Prince”. This research focuses on The Syntax Analysis and its Translation Found on Sentence Patterns in the Novel entitled “The Prince”. This study aims at analyzing the tree diagram structure and the types of translation shifts found in the novel entitled “The Prince”. In analyzing data, this study applied the theory of sentence patterns proposed by Quirk and Greenbaum and the theory of translations shift proposed by Catford. In the method and technique of collecting data, the process of collecting data was started by reading the entire data source to get the story in the novel entitled “The Prince” and observe the data of sentence patterns that can be taken from the story entitled “The Prince”. Then, the data source was read to get simple sentence patterns found in the data source. This research study found that there are seven sentence patterns translated by using unit shift of translation proposed by Catford. The researcher applied the theory of syntax, types of sentences, sentence pattern, tree diagram, and reviewed the previous studies. The implication of the study is that it can give the understanding of translation analysis found in the data source and can be used as teaching materials